Theoretical aspects of the criminal-legal protection in the field of intellectual property (Journal of actual problems of jurisprudence, 2018)
In the work of the integrated studies on theoretical and practical issues of criminal liability for violation of copyright, related, patent and inventive rights carried out with taking into account the new part 4 HC RK. In addition are considered in deep historical analysis of criminal law of Kazakhstan, the stipulating punishment for violation of the above rights; in comparative analysis of foreign criminal law and the criminal law of Kazakhstan in the sphere of human rights; in the development of scientifically based recommendations for improving legislation and practice in this area of criminal law for the protection of intellectual property. Key words: property, intellectual, rulemaking, responsibility, punishment.